Integrasi Literasi Kitab Kuning dan Evaluasi Tradisional dalam Pendidikan Santri Putri: Studi Kasus Pesantren Zainul Hasan Genggong - Hasan Firghol Muttaqien, Moh.; Shinta Kurnia Ilahi, Dewi; Dwi Irmawati Setiawan Putri, Indra; Muhammad, Begi; Anam, Khairul; Romli, M (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study critically examines the integrative role of the yellow book literacy program, tradition-based evaluation systems, and pesantren spirituality practices in shaping the scholarly character of female santri. The aim of this research is to understand how these three elements interact and contribute to the distinctive educational process within Islamic boarding schools for girls. Using a qualitative-descriptive approach and participatory observation techniques, this research gathers in-depth data from the daily practices of students and administrators. The findings indicate that the literacy system based on nadhom and the muḥāfaẓah-based evaluation not only serve as tools for knowledge transmission but also function as mechanisms for internalizing pesantren values and spirituality. This study highlights the importance of a holistic approach in Islamic education, in which literacy methods, traditions, and evaluation systems are interrelated in forming knowledgeable and virtuous santri.